Aerobic capacity is related to repeated sprint ability with sprint distances less than 40 meters. - Sanders, G. J.; Turner, Z.; Boos, B.; Peacock, C.; Peveler, W.; Lipping, A. (International Journal of Exercise Science, 2016)
Research is inconclusive regarding the association between aerobic fitness (objectively measured VO2max) and repeated sprint performance when the sprints are less than 40 meters. Soccer athletes must be ableto repeat sprints without significant decreases in speed and strength and conditioning coaches need to better understand if aerobic fitness is related to repeated sprint ability (RSA).Twenty (10 male, 10 female) Division I soccer athletes first completeda graded maximal treadmill test to measure VO2max. Then on a separate day, athletes completed the RSA test. The RSA test consisted of 10, 30-meter sprints which athletes repeated every 30 seconds. There were significant negative correlations (relations (r=-0.69, P< 0.001) between VO2maxand all 10-sprint times and average sprint time. More aerobically fit Division I soccer athletes were faster at all time points during the RSA test. Aerobic fitness is associated with faster sprint times during a more anaerobic RSA test whensprint distances areless than 40 meters.